Chemotherapy, Radiotherapy, PET and Maintenance Therapy for Lymphoma - Vinall, Maria (MD Conference Express, 2013)
This article provides insights into multiple therapies and treatments for lymphoma. Specific discussions include role of radiotherapy (RT) for the treatment of Hodgkin lymphoma, the RAPID [NCT00282035] trial, the predictive values of positron emission tomography (PET), an update on maintenance therapy in hematological malignancies, the PRIMA [NCT00140582] trial, as well as the use of Fluorodeoxyglucose-PET for the diagnosis, restaging, and follow-up in patients with lymphoma.